Foot care and footwear practices among patients attending a specialist diabetes clinic in Jamaica - Krystal A.T. Gayle; Marshall K. Tulloch-Reid; Novie O. Younger; Damian K. Francis; Shelly R. McFarlane; Rosemarie A. Wright-Pascoe; Michael S. Boyne; Rainford J. Wilks; Trevor S. Ferguson (Clinics and Practice, 2012)
This study aimed to estimate the proportion of patients at the University Hospital of the West Indies (UHWI) Diabetes Clinic who engage in recommended foot care and footwear practices. Seventy-two participants from the UHWI Diabetes Clinic completed an interviewer-administered questionnaire on foot care practices and types of footwear worn. Participants were a subset of a sex-stratified random sample of clinic attendees and were interviewed in 2010. Data analysis included frequency estimates of the various foot care practices and types of footwear worn. Participants had a mean age of 57.0±14.3 years and mean duration of diabetes of 17.0±10.3 years. Fifty-three percent of participants reported being taught how to care for their feet, while daily foot inspection was performed by approximately 60% of participants. Most participants (90%) reported daily use of moisturizing lotion on the feet but almost 50% used lotion between the toes. In conclusion, approximately 85% of participants reported wearing shoes or slippers both indoors and outdoors but over 40% reported walking barefoot at some time. Thirteen percent wore special shoes for diabetes while over 80% wore shoes without socks at some time. Although much larger proportions reported wearing broad round toe shoes (82%) or leather shoes (64%), fairly high proportions reported wearing pointed toe shoes (39%), and 43% of women wore high heel shoes. Approximately 60% of patients at the UHWI diabetic clinic engage in daily foot inspection and other recommended practices, but fairly high proportions reported foot care or footwear choices that should be avoided.